Immunogenicity and Reactogenicity of SARS-CoV-2 Vaccines in Patients With Cancer: The CANVAX Cohort Study. Issue 1 (1st January 2022) - Naranbhai, Vivek; Pernat, Claire A.; Gavralidis, Alexander; St Denis, Kerri J.; Lam, Evan C.; Spring, Laura M.; Isakoff, Steven J.; Farmer, Jocelyn R.; Zubiri, Leyre; Hobbs, Gabriela S.; How, Joan; Brunner, Andrew M.; et al.
Abstract : PURPOSE: The immunogenicity and reactogenicity of SARS-CoV-2 vaccines in patients with cancer are poorly understood. METHODS: We performed a prospective cohort study of adults with solid-organ or hematologic cancers to evaluate anti–SARS-CoV-2 immunoglobulin A/M/G spike antibodies, neutralization, and reactogenicity ≥ 7 days following two doses of mRNA-1273, BNT162b2, or one dose of Ad26.COV2.S. We analyzed responses by multivariate regression and included data from 1, 638 healthy controls, previously reported, for comparison. RESULTS: Between April and July 2021, we enrolled 1, 001 patients; 762 were eligible for analysis (656 had neutralization measured). mRNA-1273 was the most immunogenic (log10 geometric mean concentration [GMC] 2.9, log10 geometric mean neutralization titer [GMT] 2.3), followed by BNT162b2 (GMC 2.4; GMT 1.9) and Ad26.COV2.S (GMC 1.5; GMT 1.4; P < .001). The proportion of low neutralization (< 20% of convalescent titers) among Ad26.COV2.S recipients was 69.9%. Prior COVID-19 infection (in 7.1% of the cohort) was associated with higher responses ( P < .001). Antibody titers and neutralization were quantitatively lower in patients with cancer than in comparable healthy controls, regardless of vaccine type ( P < .001). Receipt of chemotherapy in the prior year or current steroids were associated with lower antibody levels and immune checkpoint blockade with higher neutralization. Systemic reactogenicity varied by vaccine and correlated with immune responses ( P = .002 for concentration, P = .016 for neutralization). In 32 patients who received an additional vaccine dose, side effects were similar to prior doses, and 30 of 32 demonstrated increased antibody titers (GMC 1.05 before additional dose, 3.17 after dose). CONCLUSION: Immune responses to SARS-CoV-2 vaccines are modestly impaired in patients with cancer. These data suggest utility of antibody testing to identify patients for whom additional vaccine doses may be effective and appropriate, although larger prospective studies are needed. Abstract :